Peran Industri Konveksi Bordir Kamen Khas Bali dalam Meningkatkan Perekonomian Masyarakat Desa Kates - Mochamad Andrew Daffa Renaldy; Bagus Setiawan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Small and medium-sized enterprises (SMEs) play a strategic role in national economic development, particularly in rural areas. Their existence not only supports local economic growth but also contributes to cultural preservation. One concrete example is the Balinese kamen embroidery convection industry that is developing in Kates Village, Kauman District, Tulungagung Regency. This industry not only produces products that represent local cultural identity but also serves as a primary source of livelihood for a large portion of the local community. This study aims to examine the role and impact of this embroidery convection industry on improving the economic conditions of the Kates Village community. The study used a descriptive qualitative approach with a field study method, where data were collected through direct observation techniques, in-depth interviews with village officials, convection business owners, workers, and local residents, as well as documentation related to production activities. The results show that this industry is able to absorb a significant local workforce, both among women and youth, thereby reducing unemployment. Furthermore, community incomes have increased, directly impacting families' living standards. Furthermore, the existence of this industry has also encouraged the growth of new entrepreneurs, both in the convection sector and other supporting sectors such as distribution and marketing. Overall, the Balinese kamen embroidery convection industry in Kates Village has proven to be a local economic force based on culture. Its potential to strengthen the people's economy is enormous, especially if developed in a targeted and sustainable manner through policy support and capacity building of business actors. Therefore, greater attention from the government and other stakeholders is needed to ensure this industry continues to grow and provides long-term positive impacts for the community.